Kekerasan Struktural dan Ketidakadilan Sosial dalam Novel Die Judenbuche Karya Annette von Droste-Hülshoff - Hilda Septriani; Kamelia Gantrisia (J-EDu Journal - Erfolgreicher Deutschunterricht, 2026)
This study examines the representation of violence and social injustice in Annette von Droste-Hülshoff’s novella Die Judenbuche (1842) through the lens of literary sociology. Using a qualitative descriptive approach, this research analyzes narrative elements, character dynamics, and community structures in the text to reveal how violence direct, structural, and cultural operates as a systemic product rather than a matter of individual moral failure. The findings show that the protagonist Friedrich Mergel’s trajectory is shaped by poverty, deprivation of social recognition, and the absence of protective institutions in nineteenth-century rural Germany. Social injustice manifests on multiple interlocking levels such as class-based discrimination and stigmatization, the complicity of a community that normalizes impunity through collective silence, and the structural invisibility of Jewish victims such as Aaron. Drawing on sociological literary theory (Wellek and Warren; Goldmann; Galtung) and key prior studies (Haryati, 2015; Doerr, 1994; Donahue, 1999), this paper argues that Droste-Hülshoff writing from the margins of a patriarchal literary canon uses narrative irony, psychological precision, and symbolic setting to mount a systemic critique of a society that reproduces inequality across generations. The killing of Aaron is read not as an act of personal vengeance but as an attempt to destroy a living mirror of Friedrich’s own humiliation a reading that foregrounds the structural rather than moral dimensions of violence. The analysis contributes to studies on German Biedermeier literature and the literary representation of marginalized communities.